Answer:
2NaHCO3(aq)+H2SO4(aq)→Na2SO4(aq)+2CO2(g)+2H2O(l)
Explanation:
As we know that
acid + carbonate → salt + carbon dioxide + water
So, the general (un-balanced) equation would be-
NaHCO3(aq)+H2SO4(aq)→Na2SO4(aq)+CO2(g)+H2O(l)
Now we will write the net ionic reactions
[tex]HCO_3^-+ H3O^+[/tex] ----> CO2(g)↑+2H2O(l)
[tex]Na ---> Na^+ + e^-[/tex]
[tex]2H^+ + 2e^- ---> H2[/tex]
[tex]SO_4^{2-} ---- SO_4 + 2e^-[/tex]
Adding all the above equation, we get
2NaHCO3(aq)+H2SO4(aq)→Na2SO4(aq)+2CO2(g)+2H2O(l)